Engineers, architects, doctors and madness. The construction Of the colonia de la magdalena asylum (1896-1918) - Amaya Núñez, Elías (2019)
The following article addresses the configuration and construction of the first modern psychiatric hospital of Peru. It focuses on the actions executed by the doctors, engineers and architects who participated in this project. The study period begins in 1896, when the Ministry of Development called for a public tender in order to receive the best proposals for the construction of a House of the Insane that could replace the Cercado Asylum; it ends in 1918 with the inauguration of Colonia de la Magdalena Asylum or Victor Larco Herrera Hospital. The article is divided into two parts. The first section describes the importance of the technical and medical professionals in the modernization process of the late nineteenth and early twentieth centuries. Furthermore, it describes the role played by the Ministry of Development and the Public Charity Society of Lima in said process. Finally, the characteristics of project that won the above-mentioned tender are shown. In the second section, the article analyzes the construction process of the General Asylum, paying attention to the dialogue that takes place between the participating agents (engineers, architects and doctors).